The abundance of soil bacteria applied with compost and Trichoderma sp. in tangerine orchard - Siswadi, Edi; Sulistyono, Nantil Bambang Eko; Firgiyanto, Refa; Dinata, Gallyndra Fatkhu; Rohman, Hanif Fatur; Rohman, Fadil (AGROMIX, 2024)
.